Chronic low back pain and muscle activity in women during the sit-to-stand task: A cross-sectional study - Thomaz de Aquino Nava, Guilherme [UNESP]; Mendes Tozim, Beatriz [UNESP]; Hebling Spinoso, Deborah [UNESP]; Baldini Prudencio, Caroline [UNESP]; Tavella Navega, Marcelo [UNESP] (My University, 2024)
Introduction: The ability to stand up and sit down is important. Due to the large number of repetitions of these activities during the day and the demand that the task requires, it is cited as painful in the presence of low back pain (LBP). Individuals with LBP present alterations in muscle activation, however, this statement needs to be verified during everyday situations like the sit-to-stand task (STST). Therefore, the objective was to evaluate the muscle recruitment of women with and without LBP during the STST. Methods: 35 women were evaluated, and allocated into the control group (CG n = 15) and the low back pain group (LBPG n = 20). The protocol consisted of clinical evaluation and the sit-to-stand task (STST). Electromyographic signals of the lumbar multifidus (LM), internal oblique (IO) and external oblique (EO), rectus abdominis (RA), and lumbar iliocostalis (LI) were carried out concomitantly with the STST. To verify normality, the Shapiro-Wilk test was used. For the characterization of the sample, the MANOVA test was chosen and the MANCOVA test was also chosen to compare the characteristics of the participants. Results: Regarding the data analysis of the electromyographic signals, higher values were seen in the RA (moments 2 and 3) in the LBPG in the STST. Conclusion: The present study showed that women with chronic LBP present higher muscle activation of the rectus abdominis in the sit-to-stand task.
Keywords: Abdominal muscles; Back muscles; Electromyography; Low back pain